MODEL OF SOCIAL RESPONSIBILITY AS A FORM OF SOCIETY AND STATE INTERACTION - Vykhovanets, Zorinа (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. State independence of Ukraine since 1991 has become a new fact of the social history of the mankind. Alongside, a number of problems in priority areas of development, structural contradictions, which solution the fate of Ukrainian statehood depends on, have emerged. The state process in Ukraine is a post-classical scenario of a political and legal process, analogs of which in world practice are almost impossible to find, therefore the relevance of the topic we have chosen is indisputable. The aim is to analyze the model of social responsibility as a form of interaction between society and a state in the context of globalization. Research methodology was determined by the complexity of the purpose of the study of social responsibility in a modern democratic society, which caused the application of interdisciplinary approaches to such areas of research as socio-philosophical and political-legal, we applied the principles of determinism, development and relationship, historical and logical unity. The basic methods are comparative and systematic analysis, structural fundamental, and functional instrumental approaches. Research results. The modern model of social responsibility is formed in the process of selforganization of citizens and the establishment of a constructive dialogue between government and civil society, which ensures the achievement of systemic capital of the social optimum. This mechanism of interaction should include two interdependent levels of functional instrumental determinants. The first level is the existence of such conceptual positions as the capacity of civil society and the rule of law, the power of the rule of law, and respect for democracy. The second level provides public practice of environmental security, national health, spiritual and religious freedom, social justice and individual rights. The conceptual interaction of these levels provides the formation of sociolegal and value-semantic basis of the social genesis of modernity. Discussion. Appeal to the works by V. Vynnychenko, M. Hrushevskyi, D. Dontsov, M. Drahomanov, P. Lypynsky, D. Chyzhevskyi and others testifies the constant and continuous search for Ukrainian humanities in the field of a state and a political nation formation. In the context of modern humanitarian discourse, the works of such foreign scholars as H. Arendt, Z. Brzezinski, M. Weber, J. Habermas, N. Luhmann, F. Hayek, and others were used. Among the scientists who have some experience in this field of scientific knowledge, we should note the works by V. Andrushchenko, V. Babkin, V. Voronkova, E. Gerasimova, O. Eremenko, V. Otreshko, M. Popovych, V. Stepiko, N. Yakovenko and others. Conclusion. Man’s existence in a state always has a specific "borderline" nature: law social relations primarily rationalize it; between them irrational "gaps" are constantly formed. Therefore, the functioning of a state order at the level of legality historically appears as a wavy line, which periodically deviates in the direction of creative reform of laws, it may be on the verge of usurpation of power or in a state of political disintegration. Such conflicts of human life in the current system of public order require constant improvement of the mechanism of social responsibility in order to ensure multi-vector optimal relationships with other players in today’s globalized world.